1993
DOI: 10.1002/ar.1092370110
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative morphological changes in neurons and glia in the frontal lobe of the aging rat

Abstract: The quantitative morphological changes in neurons and glia during the aging process were analyzed in the different cortical layers, grouped as I, II-IV, V, and VI, of the frontal cortex of the rat. The parameters analyzed were cortical volume, neuronal density, glial density, and neuronal soma and nucleus areas. No changes with age were found in the volume of the layers, in neuronal density (with the exception of layer I), or in the area of the neuronal soma. However, older animals showed a 10 to 20% increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
25
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 29 publications
4
25
0
Order By: Relevance
“…In an earlier study, using the same methods and animal model as in the present work, we found no changes in neuronal density in the frontal cortex with age, with the exception of layer I. In addition, our data for perikaryon size showed no significant changes with age, although neuronal nuclear area was reduced (Peinado et al, 1993).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In an earlier study, using the same methods and animal model as in the present work, we found no changes in neuronal density in the frontal cortex with age, with the exception of layer I. In addition, our data for perikaryon size showed no significant changes with age, although neuronal nuclear area was reduced (Peinado et al, 1993).…”
Section: Discussionsupporting
confidence: 64%
“…In the rat substantia nigra, cell loss is not as prominent as has been reported in humans (Morgan et al, 1987). However, an earlier study (Peinado et al, 1993) found no evidence of neuronal loss, which confirmed similar findings in cortical barrels of aged mice (Curcio and Coleman, 1982).…”
supporting
confidence: 81%
“…Considering that astrocytes contain a threefold to fourfold lower amount of mitochondria than neurons (Alano et al 2007), their eventual slight increase with aging should not particularly affect the content of mtDNA and of mitochondrial proteins such as TFAM. For what concerns neurons, it is now widely accepted that brain aging does not imply a loss of neurons, especially in the rat frontal cortex, but rather structural changes of neurons that alter their function (Grill and Riddle 2002;Peinado et al 1993;Turlejski and Djavadian 2002). Therefore, we can conclude that the changes in TFAM and mtDNA content are not the result of a variation in cellular population during aging, but are truly due to the effect of age.…”
Section: Discussionmentioning
confidence: 82%
“…1991; Peinado et al, 1993;Rance et al, 1993). We also analysed shape parameters such as form factor with values ranging from 0 to 1, the latter being the definition of a sphere.…”
Section: Discussionmentioning
confidence: 99%
“…Thus there is no agreement regarding the different parameters currently under study, e.g., neuronal size, extension of the dendritic tree, or the number of synapses per cell (Curcio and Hinds, 1983;Coleman and Flood, 1986;Markus et al, 1987;Flood and Coleman, 1988;de Lacalle et al, 1991;Crespo et al, 1992;Stroessner-Johnson et al, 1992;Flood and Coleman, 1993;Peinado et al, 1993;Rance et al, 1993). Similarly, it is argued whether or not neuronal loss occurs during old age (Diamond et al, 1977;Curcio and Coleman, 1982;Satorre et al, 1985;Sturrock, 1989).…”
mentioning
confidence: 99%